PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE CIRC (COOPERATIVE, INTEGRATED, READING, AND COMPOSITION) UNTUK MENINGKATKAN HASIL DAN AKTIVITAS BELAJAR MATERI POKOK KEGIATAN EKONOMI KELAS VII-B MATA PELAJARAN IPS DI MTS KYAI MAS PRAJEKAN - Ririn Aprilianti; Lisma Dian Kartika Sari (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2016)
CIRC inwrought composition reads (to realize matter contents) and write (to do exercise) cooperatively (group). Model quantity on the market researcher wants to detect applications CIRC. initially, type CIRC applied in language study. in little group, students is given a text or reading (matter), then practice student reads or mutual read, realize main idea, mutual merevisi, and write matter summary, or give conception towards matter contents, or to prepare certain task from teacher. The indicator read matter contents, co-operative and write (to do exercise). based on background on, so problem formulation as follows: 1) is applications type co-operative study model CIRC (cooperative, integrated, reading, and composition) can increase result learn class economic activity direct material VII-B subject IPS at MTs Kyai Mas Prajekan? , 2) is applications type co-operative study model CIRC (cooperative, integrated, reading, and composition) can increase activity learn class economic activity direct material VII-B subject IPS at MTs Kyai Mas Prajekan? Research design in this Research CAR with berkolaborasi with teacher that appointeds 2 cycles. In CAR there 4 stages that is planning, action, observation and reflection. Primary data by using repetition test and observation with at checklist, and secondary data with interview. Researcher uses target value necessity determine successful criteria to analyzes data. Based on Research result at chapter iv inferential as follows: 1) type co-operative study model applications CIRC (cooperative, integrated, reading, and composition) can increase result learn as big as 88% class economic activity direct material VII-B subject IPS at MTs Kyai Mas Prajekan; 2) type co-operative study model applications CIRC (cooperative, integrated, reading, and composition) can increase activity learn as big as 89% class economic activity direct material VII-B subject IPS at MTs Kyai Mas Prajekan.